Community Governance and Socio-Economic Development Realities in Nigeria - Lamidi, Kazeem Oyedele; Etebom, John Monday (African Journal of Stability and Development (AJSD), 2022)
This paper explores the nexus between community governance and the realities of socio-economic development at the local level. This work relies on secondary data. The paper reveals that institutional frameworks at community level have potentialities in the realisation of socio-economic development in Nigeria. The paper recommends that extensive national value re-orientation and spirit of communalism are the needed mechanisms that would inspire patriotic citizenship/leadership and active civil society which is able to drive the process of utilising both local human and natural resources for the actualisation of socio-economic development in Nigeria.